EDUCATIONAL TECHNOLOGY POLEMIC: LECTURER COMPETENCE - Santi Kurnia; Dwi Astuti (SEAN Institute, 2023)
In the field of education, the influence of educational technology and information literacy on faculty competence is a topic of critical importance. As the use of technology and access to information increases, it is essential that faculty possess the necessary skills and competencies to effectively incorporate these tools into their teaching practices. The use of educational technology and information literacy has been shown to increase faculty competence by enhancing their knowledge and abilities in areas such as pedagogy, curriculum development, and assessment. In addition, the faculty's ability to effectively use and access information can assist them in keeping abreast of the latest research and best practices in their respective fields, thereby enhancing the quality of their instruction and their overall effectiveness as educators. The use of educational technology and information literacy can have a positive impact on faculty competency and contribute to the success of the institution as a whole.